Inverse scattering properties with Levinson formula for cubic eigenparameter-dependent discrete Dirac problem - Koprubasi, Turhan; Mohapatra, R. N. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We present some properties of zeros of the Jost function and of the scattering function. Then the uniqueness of the kernel and the continuity of the scattering function with appropriate Levinson-type formula are investigated for the inverse discrete Dirac problem based on the cubic eigenparameter-dependent boundary condition.